Epidemiological profile of abortions in the southwest region of mato grosso - proposal for a new flowchart of care (Research, Society and Development, 2020)
Spontaneous abortion is a major public health problem, usually occurring in the first 12 weeks of pregnancy, and is often underreported. In Brazil, there is currently no flowchart of care for patients diagnosed with initial pregnancy undergoing abortion recommended by the Ministry of Health. Recognizing the epidemiological profile and characterizing patients with early abortion, allows to act in primary prevention, directing resources and optimizing primary care . The objective of this study was to analyze the epidemiological profile of patients diagnosed with spontaneous abortion in the Southwest region of Mato Grosso between January 2018 and July 2019, analyzing the clinical forms of early abortion and its prevalence. Cross-sectional study with secondary data of pregnant women hospitalized for spontaneous abortion, extracted after approval by the ethics committee of medical records and clinical files and later transferred for data analysis in the SPSS software. In total, 348 patients were included, the average age was 29.36 years, the most common ethnicity was mixed race, 56% were single. Most patients had no information described or accurate in the medical record regarding occupation, education, prenatal care and medication use. Once the incompleteness of information and the importance of the data have been verified, systematizing data collection in the medical records of hospitalized patients diagnosed with early abortion is of paramount importance. Based on an effective intervention in the care protocol for these patients, it will be possible to assess risk groups for the development of unfavorable outcomes, which will enable targeted and accurate primary prevention.